Sono‐Controllable and ROS‐Sensitive CRISPR‐Cas9 Genome Editing for Augmented/Synergistic Ultrasound Tumor Nanotherapy - Pu, Yinying; Yin, Haohao; Dong, Caihong; Xiang, Huijing; Wu, Wencheng; Zhou, Bangguo; Du, Dou; Chen, Yu; Xu, Huixiong (Advanced materials (Weinheim), 2021)
The potential of the cluster regularly interspaced short palindromic repeat (CRISPR)‐associated protein 9 (Cas9)‐based therapeutic genome editing is severely hampered by the difficulties in precise regulation of the in vivo activity of the CRISPR‐Cas9 system. Herein, sono‐controllable and reactive oxygen species (ROS)‐sensitive sonosensitizer‐integrated metal–organic frameworks (MOFs), denoted as P/M@CasMTH1, are developed for augmented sonodynamic therapy (SDT) efficacy using the genome‐editing technology. P/M@CasMTH1 nanoparticles comprise singlet oxygen (1O2)‐generating MOF structures anchored with CRISPR‐Cas9 systems via 1O2‐cleavable linkers, which serve not only as a delivery vector of CRISPR‐Cas9 targeting MTH1, but also as a sonoregulator to spatiotemporally activate the genome editing. P/M@CasMTH1 escapes from the lysosomes, harvests the ultrasound (US) energy and converts it into abundant 1O2 to induce SDT. The generated ROS subsequently trigger cleavage of ROS‐responsive thioether bonds, thus inducing controllable release of the CRISPR‐Cas9 system and initiation of genome editing. The genomic disruption of MTH1 conspicuously augments the therapeutic efficacy of SDT by destroying the self‐defense system in tumor cells, thereby causing cellular apoptosis and tumor suppression. This therapeutic strategy for synergistic MTH1 disruption and abundant 1O2 generation provides a paradigm for augmenting SDT efficacy based on the emerging nanomedicine‐enabled genome‐editing technology. A novel avenue to circumvent the resistance of tumor cells in conventional sonodynamic therapy is pioneered in this work, where targeted delivery and controllable release of the cluster regularly interspaced short palindromic repeat‐associated protein system is also achieved.